Effets du drainage ameliore et de l'application d'engrais sur la croissance de l'ivraie multiflore et de l'avoine sur un sol a proprietes vertiques a Debre Berhan, Ethiopie - Haque, I.; Jutzi, S.C. (1984)
Summarizes and discusses the results of an experiment carried out in 1983 with oats and Italian ryegrass on a soil with vertic properties near Debre Berhan area (Ethiopia) to examine the effects of improved drainage and fertilization (N/P).